2008
DOI: 10.1097/01.nna.0000295629.95592.78
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Spiritual Leadership

Abstract: The Joint Commission requires health systems to address spiritual care. Research indicates that spirituality is associated with better physical, psychological, and social health and that culturally diverse populations and individuals at end-of-life often request spiritual care. The authors report the results of a consensus conference of 21 executives representing 10 large faith-based health systems who discussed the input, process, and outcomes of a corporate model for spiritual leadership. Specific initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…SL is a set of human values that constitute the working environment of an organization, where its employees demonstrate their abilities and skills (Burkhart, 2008).…”
Section: Spiritual Leadership Conceptmentioning
confidence: 99%
“…SL is a set of human values that constitute the working environment of an organization, where its employees demonstrate their abilities and skills (Burkhart, 2008).…”
Section: Spiritual Leadership Conceptmentioning
confidence: 99%
“…F or over a decade, the Joint Commission on Accreditation of Healthcare Organizations has recognized the importance of addressing spirituality in the care of patients (Burkhardt, Solari-Twadell, & Hass, 2008). For those with substance use disorders, spirituality is a frequently acknowledged significant contributor to recovery.…”
mentioning
confidence: 99%
“…In an earlier report, the Center for Research on Religion and Urban Civil Society/Gallup Spiritual Index found that 68% of Americans desire spiritual growth and rely on their faith for meaning (Gallup & Johnson, 2003). Burkhardt et al (2008) report that, in 2004, 64% of U.S. citizens reported using some type of complementary and alternative medicine as part of their health care. Burkhardt et al (2008) report that, in 2004, 64% of U.S. citizens reported using some type of complementary and alternative medicine as part of their health care.…”
mentioning
confidence: 99%
“…A number of different strategies and programmes were proposed in the literature review from a non‐denominational blessing of the hands (Wolpert ); to mindfulness (Pipe & Bortz ) or reflective (Burkhart et al . ) practices; and to workshops that taught spiritual strategies such as holy word repetitions, focusing, inspirational readings, sense training and character disciplines (Yong et al . ).…”
Section: Philosophic Inquirymentioning
confidence: 99%